2014
DOI: 10.1068/a46236
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Intangible Assets on Regional Productivity Disparities in Great Britain

Abstract: During the past few years there has been a growing consensus in the literature that intangible assets represent a major source of productivity growth. Intangibles facilitate the accumulation of knowledge and information via learning and innovation, allowing, in this way, modern economies to improve the efficiency with which they utilise their resources. Nonetheless, despite the proliferation of studies that investigate the territorial impact of intangibles (variously defined), the full effect of these assets o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…They may even be counterbalanced by negative externalities of larger cities and core regions (Broersma and van Dijk, 2008; Harris et al., 2011). To understand the variation in regional productivity fully, scholars have underlined the increase in aggregate productivity and income in the presence of higher skill levels, pointing to the importance of human capital (Abel, Dey and Gabe, 2012; Marrocu and Paci, 2012; Melachroinos and Spence, 2014; Rosenthal and Strange, 2008) and the tendency of more skilled workers to live in densely populated areas (Di Giacinto et al., 2014; Glaeser and Resseger, 2010). Indeed, complementary national and firm-level evidence indicates low levels of skills negatively impact productivity and growth (Crafts and O’Mahoney, 2001; Machin, Vignoles and Galindo-Rueda, 2003; Webber, Boddy and Plumridge, 2007; Wixe, 2015), while regional level evidence has also shown that the positive relationship between productivity and the effect of agglomeration externalities is stronger in more skilled areas (Glaeser and Resseger, 2010; Harris and Moffat, 2015).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…They may even be counterbalanced by negative externalities of larger cities and core regions (Broersma and van Dijk, 2008; Harris et al., 2011). To understand the variation in regional productivity fully, scholars have underlined the increase in aggregate productivity and income in the presence of higher skill levels, pointing to the importance of human capital (Abel, Dey and Gabe, 2012; Marrocu and Paci, 2012; Melachroinos and Spence, 2014; Rosenthal and Strange, 2008) and the tendency of more skilled workers to live in densely populated areas (Di Giacinto et al., 2014; Glaeser and Resseger, 2010). Indeed, complementary national and firm-level evidence indicates low levels of skills negatively impact productivity and growth (Crafts and O’Mahoney, 2001; Machin, Vignoles and Galindo-Rueda, 2003; Webber, Boddy and Plumridge, 2007; Wixe, 2015), while regional level evidence has also shown that the positive relationship between productivity and the effect of agglomeration externalities is stronger in more skilled areas (Glaeser and Resseger, 2010; Harris and Moffat, 2015).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Scholars link the heterogeneity of regional productivity with an uneven distribution of skills (Morris et al, 2019). The increase in aggregate productivity and income is connected with the presence of higher skill levels, pointing to the importance of human capital (Rosenthal and Strange, 2008;Marrocu and Paci, 2012;Abel et al, 2012;Melachroinos and Spence, 2014) and the tendency of more skilled workers to live in densely populated areas (Glaeser and Resseger, 2010;Di Giacinto et al, 2014;Noja and Cristea, 2018). Fernald and Wang (2016) add an explanation based on a softer response of employment to the cycle and to pro-cyclical factor utilization (physical capital, labour, and human capital).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Intangible assets contribute to productivity and growth within the firm, for example,, through human capital, organisational abilities, R&D activities and brand equity, as well as have implications to a broader community and economy, such as through local externalities, innovation and entrepreneurship, institutional system, social capital and trust, among others (Suriñach & Moreno, 2012). Intangibles allow to utilise resources more efficiently through accumulation of knowledge and information via learning and innovation (Melachroinos & Spence, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Being different, regions are also closely connected to each other by knowledge flows and spillover effects (Suriñach & Moreno, 2012). Regional economic growth may be associated with high level of intangible capital, or territorial/relational proximity to it (Melachroinos & Spence, 2014). In this regard, a regional focus represents a fruitful and relevant perspective for unveiling territorial aspects of intangible assets, and regional characteristics become important considerations when analysing intangibles and explaining their economic implications.…”
Section: Introductionmentioning
confidence: 99%